2006
DOI: 10.1002/masy.200651018
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Alignment of Rhodamine B Intercalated in Synthetic Mica

Abstract: Rhodamine B was intercalated in interlayer spaces of Somasif Me‐100, a synthetic mica, and the obtained rhodamine B/Somasif hybrid was suspended in a UV‐curable resin precursor. Then, the suspension was subjected to an applied rotating magnetic field to align the hybrid particles, followed by solidification of the medium by UV irradiation to fix the alignment. The hybrid particles were aligned so that the Somasif layer lay perpendicular to the axis of rotation of the applied rotating magnetic field. UV/vis mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Also known as fluoromica mineral, Somasif (SME), described by the formula Na 0.66 Mg 2.68 (Si 3.98 Al 0.02 )O 10.02 F 1.96 , is a semisynthetic crystalline clay: the high aspect ratio (of about 6000), the low charge density and the low amounts of impurities make SME highly interesting for the fabrication of advanced compounds with potential applications in polymer nanocomposites, 29 drug delivery systems 30 and feeble magnetic materials. 31 However, widespread development of dye doped SME hybrids is still a challenging task because SME has some drawbacks: (i) the clay platelets are larger than LAP, thus increasing the interplate crystalline welding, (ii) the SME suspensions undergo sedimentation and (iii) the partial replacement of -OH groups by -F reduces the hydrophilic SME character. 32 In order to overcome those issues, we propose an innovative functional polymeric hybrid based on SME that combines two of the favorable properties of SME (low charge layer density and high aspect ratio) with the unique ones of physicochemical stability, optical transparency and processability of a vinyl-end poly(norbornene) (PNB).…”
Section: Introductionmentioning
confidence: 99%
“…Also known as fluoromica mineral, Somasif (SME), described by the formula Na 0.66 Mg 2.68 (Si 3.98 Al 0.02 )O 10.02 F 1.96 , is a semisynthetic crystalline clay: the high aspect ratio (of about 6000), the low charge density and the low amounts of impurities make SME highly interesting for the fabrication of advanced compounds with potential applications in polymer nanocomposites, 29 drug delivery systems 30 and feeble magnetic materials. 31 However, widespread development of dye doped SME hybrids is still a challenging task because SME has some drawbacks: (i) the clay platelets are larger than LAP, thus increasing the interplate crystalline welding, (ii) the SME suspensions undergo sedimentation and (iii) the partial replacement of -OH groups by -F reduces the hydrophilic SME character. 32 In order to overcome those issues, we propose an innovative functional polymeric hybrid based on SME that combines two of the favorable properties of SME (low charge layer density and high aspect ratio) with the unique ones of physicochemical stability, optical transparency and processability of a vinyl-end poly(norbornene) (PNB).…”
Section: Introductionmentioning
confidence: 99%
“…Anisotropic materials that contain one or two long axes (such as crystal platelets, nanotubes, and nanorods) represent an interesting intermediate case because they have both nanoscale and microscale dimensions. Previous studies on the interaction of mica crystallites with magnetic fields have shown that they can be aligned with the layer axis perpendicular to the applied field . Uyeda and co-workers have studied tetrahedrally and octahedrally coordinated oxides, and their analysis of the diamagnetic anisotropy of individual bonding orbitals suggests that in many cases the preferential alignment direction for lamellar solids should be edge-on, i.e., in the desired arrangment for proton conducting membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the interaction of mica crystallites with magnetic fields have shown that they can be aligned with the layer axis perpendicular to the applied field. 22 Uyeda and co-workers have studied tetrahedrally and octahedrally coordinated oxides, [23][24][25] and their analysis of the diamagnetic anisotropy of individual bonding orbitals suggests that in many cases the preferential alignment direction for lamellar solids should be edge-on, i.e., in the desired arrangment for proton conducting membranes. In this paper, we report the magnetic alignment of the lamellar compound K 4-x H x Nb 6 O 17 • nH 2 O (x ≈ 2.2).…”
Section: Introductionmentioning
confidence: 99%
“…With typical values of Δχ, U m is on the order of kT in 1 T fields for particles in the micrometer size range. 23 Because of the strong dependence of U m on particle dimensions (U m ∼ V ∼ d 3 ), one does not expect diamagnetic nanoparticles to orient in 1 T fields. A key question for the preparation of ion-transporting films and membranes from oriented microparticles is the direction of diamagnetic orientation.…”
Section: ' Introductionmentioning
confidence: 99%
“…In order to obtain oriented crystals, U m must exceed the thermal energy, kT . With typical values of Δχ, U m is on the order of kT in 1 T fields for particles in the micrometer size range . Because of the strong dependence of U m on particle dimensions ( U m ∼ V ∼ d 3 ), one does not expect diamagnetic nanoparticles to orient in 1 T fields.…”
Section: Introductionmentioning
confidence: 99%